Plan de monitoreo, asesoría y supervisión pedagógica bajo el enfoque democrático para mejorar el desempeño laboral de los docentes del nivel secundario en la i.e. n° 80657 - recuaycito . la libertad - Culqui Casana, Edwin Alexander (2015)
The present research is a proposal in front of a nonexistent pedagogical supervision system, properly structured and allows coordination between different levels of management of the Ministry of Education; also seeks to clarify the ambiguous conceptual guidelines on what is and means pedagogical supervision, monitoring and counseling. The research aimed to demonstrate that the application of the monitoring plan, consultancy and pedagogical supervision under democratic approach improves job performance of teachers at the secondary level of School No. 80657 of the village of Recuaycito. We worked with a sample universe of seven teachers at the secondary level, using the experimental design no single group with pre and post test. The job performance of teachers was studied in three dimensions: planning, implementation processes and assessment processes; the same that were evaluated in the Pre test (monitoring) and the Post Test (pedagogical supervision). Finally determined in the Post Test, that 57% of teachers obtained an outstanding level and 43% a sufficient level in their job performance, thus concluding that the implementation of the Monitoring Plan, Counseling and Educational Supervision under the democratic approach managed to significantly improve job performance of teachers EI Recuaycito No. 80657 - La Libertad